Essential Readings in Light Metals, Volume 2, Aluminum Reduction Technology - Bearne, Geoff; Dupuis, Marc.; Tarcy, Gary.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
ONE OF A FOUR-BOOK COLLECTION SPOTLIGHTING CLASSIC ARTICLES Landmark research findings and reviews in aluminum reduction technology Highlighting some of the most important findings and insights reported over the past five decades, this volume features many of the best original research papers and reviews on aluminum reduction technology published from 1963 to 2011. Papers have been organized into seven themes: 1. Fundamentals 2. Modeling 3. Design 4. Operations 5. Control 6. Environmental 7. Alternative processes The first six themes deal with conventional Hall-Héroult electrolytic reduction technology, whereas the last theme features papers dedicated to nonconventional processes. Each section begins with a brief introduction and ends with a list of recommended articles for further reading, enabling researchers to explore each subject in greater depth. The papers for this volume were selected from among some 1,500 Light Metals articles. Selection was based on a rigorous review process. Among the papers, readers will find breakthroughs in science as well as papers that have had a major impact on technology. In addition, there are expert reviews summarizing our understanding of key topics at the time of publication. From basic research to advanced applications, the articles published in this volume collectively represent a complete overview of aluminum reduction technology. It will enable students, scientists, and engineers to trace the history of aluminum reduction technology and bring themselves up to date with the current state of the technology.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering